The study of the optical activity of some S-derivatives 4-R-5-((((3-(pyridin-4-yl)-1H-1,2,4-triazole-5-yl)thio)methyl)-4H-1, 2,4-triazole-3-thiols - Ye. O. Karpun; S. O. Borsuk; L. I. Kucherenko; V. V. Parchenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2022)
About half of the drugs currently produced are chiral compounds, and about 90 % of these compounds are sold as racemates, consisting of an equimolar mixture of two enantiomers. Although they have the same chemical structure, most of the optical isomers of chiral substances show marked differences in biological activity. It is known that the presence of a single asymmetric atom has become almost an integral part of advanced drug design.